Cotransductional Mapping of the trp-his Region of Bacillus megaterium - Callahan, James P. (1983)
Eight trp mutations (four trpE, two trpB, one trpC, and one trpD) have been mapped in Bacillus megaterium QM B1551 and were found to be linked to two hisH mutations and unlinked to several other his mutations.